Isolasi Rhizobakteri dan Pengaruh Aplikasinya dengan Pupuk N-P terhadap Mutu Benih dan Pertumbuhan Bibit Tetua Betina Jagung - Asih, Pitri Ratna; Surahman, Memen; Giyanto, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Increased productivity of maize can be done with the use of high quality seeds from improved varieties such as hybrid seed. The objectives of this study were Increasing productivity of maize female parent is important in order to reduce the price of hybrid seed. The objectives of this study were to determine the nitrogen fixing bacteria compatible with phosphate solubilizing bacteria (PSB), and using those bacteria to increase physiological seed quality and seedling growth of maize female parent. The research consisted of laboratory and field experiments. Laboratory experiment for the isolation and identification of rhizobacteria resulted in 25 Azotobacter and 29 Actinomycetes non-pathogenic isolates capable of fixing nitrogen and PSB selected for compatibility tests were AB3, B28, P12, P14, P24, and P31. The compatibility test showed 25 pairs of BPF with Azotobacter and 16 pairs of BPF with Actinomycetes were mutually compatible. The BPF pair with Azotobacter or Actinomycetes P24-AzL7, P24-AzL9, B28-AcCKB4, P24-AcCKB9, P24-AcCKB20, and P24-AcCKW5 were able to increase the vigor index of hybrid maize female parent seed. Field experiment was arranged in a split plot design with three replications. The main plot was dosage of N-P fertilizer (0%, 25%, 50%, 75%, and 100% of recommendation dosage), and the subplot was 12 rhizobacteria treatments selected from 25 compatible pairs of BPF with Azotobacter and 16 pairs of BPF with Actinomycetes and 1 control. The application of compatible pairs of bacteria had a significant effect on plant height, the number of leaves at 3 and 4 weeks after planting and plant dry weight. However, the best treatment i.e. B28-AcCKB4 was not significantly different with the nutrient broth treatment (as control).